Efektifitas Penggunaan Metode Pembelajaran Quantum Learning terhadap Kemampuan Pemahaman Konsep Matematis Mahasiswa - Sudarman, Satrio Wicaksono; Vahlia, Ira (Universitas Islam Raden Intan Lampung, INDONESIA, 2016)
This study was conducted to improve the mastery of student concepts on calculus materials using Quantum Learning method, this research is motivated because the learning of calculus has not seen any mastery of concept implemented during learning. Therefore formulated problems in this research is how the implementation of learning calculus by using the method of Quantum Learning, and how to increase the mastery of concepts on learning calculus mathematics by applying the method of Quantum Learning. The purpose of this study is to determine the ability to understand mathematical concepts of students who obtain learning Quantum Learning and students who obtain conventional learning. The type of research is a quasi-experiment with the design is Posttest-Only Design. The sample in this research is a student of 3rd semester of Muhammadiyah Metro University. The technique of data collecting using ability comprehension test of mathematical concept and hypothesis test using t-test. From the result of hypothesis test using t test that is tct = 4,136 and ttable = 2,035 which show at significant level α = 0,05 yield tcount> ttable and states that H0 is rejected means ability of comprehension mathematical concept of a student who gets learning of Quantum Learning is higher than student Who acquired conventional learning.